Recent Advances in Doping of Molybdenum Disulfide: Industrial Applications and Future Prospects - Pham, Viet Phuong; Yeom, Geun Young (Advanced materials (Weinheim), 2016)
Owing to their excellent physical properties, atomically thin layers of molybdenum disulfide (MoS2) have recently attracted much attention due to their nonzero‐gap property, exceptionally high electrical conductivity, good thermal stability, and excellent mechanical strength, etc. MoS2‐based devices exhibit great potential for applications in optoelectronics and energy harvesting. Here, a comprehensive review of various doping strategies is presented, including wet doping and dry doping of atomically crystalline MoS2 thin layers, and the progress made so far for their doping‐based prospective applications is also discussed. Finally, several significant research issues for the prospects of doped‐MoS2 in industry, as a guide for 2D material community, are also provided. Various strategies for doping of molybdenum disulfide are comprehensively reviewed, including wet doping and dry doping of MoS2 thin layers and the progress made so far for their doping‐based industrial applications. Finally, a few important opening study directions for future prospects of doped atomically crystalline MoS2 layers in optoelectronics and energy harvesting, as a guide for the 2D material community, are also provided.